2016
DOI: 10.1177/0265407515617705
|View full text |Cite
|
Sign up to set email alerts
|

Are problems that contribute to divorce present at the start of marriage, or do they emerge over time?

Abstract: Divorced individuals offer explanations for why their relationship ended, yet little is known about the development of these problems during the relationship. Problems that lead to divorce may exist at the beginning of the marriage (enduring dynamics model) or may develop over time (emergent distress model). We asked 40 divorced individuals about the reasons for their divorce and compared the development of problems that did and did not contribute to their divorce over the first few years of their marriage. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Again, this is consistent with the enduring dynamics model, which hypothesizes that distress and eventual dissolution results from problems that were evident at the start of marriage. Notably, husbands’ trajectory groups did not significantly differ in their rates of divorce, consistent with past research which has found that wives’ behaviors and cognitions are more strongly linked to divorce than husbands’ (e.g., Williamson, Nguyen, Bradbury, & Karney, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Again, this is consistent with the enduring dynamics model, which hypothesizes that distress and eventual dissolution results from problems that were evident at the start of marriage. Notably, husbands’ trajectory groups did not significantly differ in their rates of divorce, consistent with past research which has found that wives’ behaviors and cognitions are more strongly linked to divorce than husbands’ (e.g., Williamson, Nguyen, Bradbury, & Karney, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…From the perspective of enduring dynamics, factors that contribute to losses of marital satisfaction are stable and present at the beginning of the marriage (e.g., Williamson, Nguyen, Karney, & Bradbury, 2016). While there is no clear consensus about factors that best characterize enduring dynamics, researchers have viewed attachment styles as one relatively stable person influence on relationship satisfaction.…”
mentioning
confidence: 99%
“…In contrast to losses of positive or idealized relationship attributes emphasized in disillusionment accounts, the emergent distress perspective posits that relationship deteriorations mount over time from increased friction caused by previously overlooked problems (e.g., Clements, Cordova, Markman, & Laurenceau, 1997; Williamson et al, 2016). When partners lack interpersonal skills needed to resolve relationship conflicts and communication difficulties, antagonisms rise and grievances accumulate while relationship satisfaction erodes (Gottman, 2014).…”
mentioning
confidence: 99%
“…Extramarital affairs were the most-cited reason. Williamson, Nguyen, Bradbury andKarney (2016:1121), Allen andAtkins (2012:1478) and Amato and Preveti (2003:607) refer to extramarital affairs/infidelity as the main reason for divorce among married couples. The researchers found that most of the participants showed some distress to demonstrate how badly they were affected by infidelity.…”
Section: Financial Difficultiesmentioning
confidence: 99%